How to be Together in a Meaningful Way that Makes Sense and a Possible Difference...? : A Collaborative Approach in Working with People Striving with Substance Abuse and Addiction - Westerhof, Luuk L. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2017)
This article attempts to share some light on how we, as professionals can be together with people striving with substance abuse in a way that it makes sense and a possible difference. I will pause for a moment by the question as to how can we be together with people striving with substance abuse in a manner that our practice has relevance for them in their everyday lives? We are living in a fastchanging society and world, often too fast, by that meaning that we not always know what we mean by relevance, and who determines what is relevant? In working as a therapist with people battling drug- and alcohol addiction, I have witnessed many times that professionals possess the notion, that they know the answer to questions such as, what are proper codes in being together with…, and who defines what is relevant or not in treatment? As a clinician, I prefer a more collaborative approach - the nature of postmodern thinking, as opposed to exercise interventions. I will shed some light on how to understand psychiatry and psychotherapy as a contrast to the postmodern collaborative approach. I think it is much more fruitful when we take a humbler position in working with people, realizing that people change all the time, systems comprised by people change rapidly all the time socially, culturally, economically e.g. Instead of thinking that we know it all, we rather should acquire a more curios position in which nothing is certain but everything possible.